2014
DOI: 10.1136/openhrt-2013-000015
|View full text |Cite
|
Sign up to set email alerts
|

The reduced cost of providing a nationally recognised service for familial hypercholesterolaemia

Abstract: ObjectiveFamilial hypercholesterolaemia (FH) affects 1 in 500 people in the UK population and is associated with premature morbidity and mortality from coronary heart disease. In 2008, National Institute for Health and Care Excellence (NICE) recommended genetic testing of potential FH index cases and cascade testing of their relatives. Commissioners have been slow to respond although there is strong evidence of cost and clinical effectiveness. Our study quantifies the recent reduced cost of providing a FH serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It was assumed that 72% of those treated take atorvastatin, 20% simvastatin and 8% rosuvastatin. 16 The distribution of adult daily dosages for each medication was taken from the 2010 audit. 15 In sensitivity analysis, we modelled the impact of a reduction in the price of rosuvastatin and ezetimibe when UK patent protection ends in 2017.…”
Section: Methodsmentioning
confidence: 99%
“…It was assumed that 72% of those treated take atorvastatin, 20% simvastatin and 8% rosuvastatin. 16 The distribution of adult daily dosages for each medication was taken from the 2010 audit. 15 In sensitivity analysis, we modelled the impact of a reduction in the price of rosuvastatin and ezetimibe when UK patent protection ends in 2017.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed and robust health economic evaluation of community detection, cascade screening, genetic testing, and treatment of patients identified with FH is requisite for supporting the case for funding by government bodies. Current health economic evaluations from the Netherlands 19) , Australia 20) , and the United Kingdom 21) have shown that cascade screening, including genetic testing, is a costeffective approach to detect FH. However, healthcare systems, population characteristics, and available resources in different countries require local models of care for FH detection and care.…”
Section: Health Economicsmentioning
confidence: 99%
“…Clinical registries and decision support systems can help coordinate cascade screening and increase efficiency of healthcare services 89) . PASS clinical software has been successfully employed in Wales and the Netherlands to support FH cascade testing 21,90) . Patient registries can also be instruments for clinical research and improving healthcare planning and patient care.…”
Section: Role Of Registriesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper by Pears et al [ 31 ▪▪ ] examined the cost-effectiveness of three alternative models of care for familial hypercholesterolaemia. The first model considered was a specialist-led model.…”
Section: Cost-effectiveness Of Different Strategies For Cascade Testimentioning
confidence: 99%